New species and new records of Reteporella (Bryozoa: Cheilostomatida) from Greenland waters - Denisenko, Nina V. (Zootaxa, 2022)
New species and new records of the cheilostome bryozoan family Phidoloporidae are reported from the poorly studied shelf and continental slope of Greenland. Reteporella vitta n. sp. differs from congeners in the shape and size of fenestrulae, the size of autozooids and their arrangement within the colony, features of the orificial complex, including the indistinctly denticulate distal rim, shape of the condyles and height of the peristome, as well as the shape and location of the suboral avicularium, and the morphology of the ovicell. Reteporella obscura n. sp. differs from other Reteporella species in a unique combination of the following characters: colony surface texture, shape of orifice and condyles, shape of the suboral avicularium, and the morphology of the ovicell. Other specimens of Reteporella from Greenland were identified as R. watersi (Nordgaard, 1907), firstly recorded in southern and western parts of the study area, and as R. grimaldii (Jullien, 1903) and R. beaniana (King, 1846), previously known only from some localities of western and eastern Greenland and recorded abundantly in 2016. Reteporella watersi specimens from Greenland differ from conspecific material from the Faroe Islands in lacking oral spines and in the size of zooidal characters.